Profile of Nutritional and Quality Aspects of Wild African Catfish, Clarias Gariepinus (Burchell, 1822) in Assiut, Egypt - Abd-Allah, Sherief Mohammed Sayed (International Journal For Research In Agricultural And Food Science, 2019)
The present study aimed at detecting some aspects of the nutritional, physicochemical and bacterial quality of the fresh African catfish (Clarias gariepinus) obtained from fish sellers at Assuit city, Egypt. A sum of 65 samples was randomly collected over a period of 2 months. The samples were subjected to sensory evaluation; the proximate composition “dry matter, moisture, protein, fat, and ash %”, pH, TVB, and TBARS were estimated; carbohydrate% and gross energy values were calculated; coliforms, fecal coliforms, E. coli, Cl. perfringens, and Aeromonas spp. count was determined. The estimated mean values (%) of dry matter, moisture, protein, fat, ash, and carbohydrates of the examined catfish samples were 23.69±0.39, 76.31±0.39, 17.97±0.16, 3.97±0.35, 1.18±0.02, and 0.57±0.02, respectively. The gross energy values (Kcal/100g) ranged from 70.65 to 187.14 with mean of 109.86±3.20. The mean values of energy (Kcal/100g) derived from fat, protein, and carbohydrates were 35.7±5.12, 71.89±0.63, and 2.27±0.09, respectively. The sensory scores of the samples ranged from 1.67 to 2.9 with mean of 2.79±0.03. The mean values of pH, TVB (mg N/100g fish flesh), and TBARS (mg malonaldehyde/kg fish flesh) were 6.94±0.03, 20.71±0.52, and 1.33±0.11, respectively. The coliforms and fecal coliforms were detected in 93.85% and 23.08% of the examined samples, respectively, while E. coli and Clostridium perfringens was detected each in only 3.08% of the examined samples. The Aeromonas count was recorded in 75.39% of the samples, with a mean count of 1.84±0.08 log cfu/g. All of the examined catfish samples showed TVB and TBARS values within the permissible limits. Coliforms count exceeded the permissible limit in 20% of the examined samples. In conclusion, catfish sold in Assiut fresh fish markets is of good nutritional, sensory and physicochemical quality; however its bacterial quality is suspicious as it may harbor potentially pathogenic or pathogenic bacteria. Thorough cooking is required before consumption to avoid public health hazard.